2022
DOI: 10.3390/fib10080066
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Atmospheric Plasma/UV Laser Treatment on the Chemical and Physical Properties of Cotton and Polyester Fabrics

Abstract: Atmospheric plasma treatment can modify fabric surfaces without affecting their bulk properties. One recently developed, novel variant combines both plasma and UV laser energy sources as a means of energising fibre surfaces. Using this system, the two most commonly used fibres, cotton and polyester, have been studied to assess how respective fabric surfaces were influenced by plasma power dosage, atmosphere composition and the effects of the presence or absence of UV laser (308 nm XeCl) energy. Plasma/UV expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…The effect of ozone or plasma treatment may cause slight erosion in the surfaces of fibers, favoring the adhesion of small particles. In the case of plasma, Peran and Razic [ 38 ] and Ayesh et al [ 39 ] stated that the effect of the plasma is dependent of the conditions under which the fiber is exposed in the treatment. Similarly, Lou et al [ 40 ] demonstrated that ozone affects the surface morphology of polyester fibers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of ozone or plasma treatment may cause slight erosion in the surfaces of fibers, favoring the adhesion of small particles. In the case of plasma, Peran and Razic [ 38 ] and Ayesh et al [ 39 ] stated that the effect of the plasma is dependent of the conditions under which the fiber is exposed in the treatment. Similarly, Lou et al [ 40 ] demonstrated that ozone affects the surface morphology of polyester fibers.…”
Section: Resultsmentioning
confidence: 99%
“…The retention power of microcapsules is higher when PES is treated with plasma than when it is treated with ozone. The pre-treatments can cause roughness on fiber surfaces and can improve some proprieties in polyester molecules [ 39 ], which can change the affinity with lavender oil, which in turn can delay the release of the active principle.…”
Section: Resultsmentioning
confidence: 99%
“…These dimensional and shape differences may affect ber packing and pore quality. According to a literature report, pore structures in brous materials depend signi cantly on the ber types and the methods of assembly [44]. Similarly, CO fabric displayed more irregular and non-uniform cross-sectional intensities that resonated between 0 and 160 pixels for both horizontal and vertical axes, while PES fabric shows a relatively smoother and more evenly distributed cross-sectional structure that varies between 60 and 100 pixels on both vertical and horizontal axes.…”
Section: Morphological Assessmentmentioning
confidence: 99%
“…The literature shows a decrease in the tear and tensile strength of surface-modified denim fabrics. 20 The influence of the laser beam, this time of the ultraviolet (UV) type, on the physical and chemical properties of polyester as well as cotton fabrics was also investigated by Ayesh et al 21 Kan 22 in another study describes the results of his research on the modification of textile properties of polyester with the use of a laser beam, taking into account the characteristics of materials. It shows the positive influence of the laser on the wettability and air permeability of the fabric as well as the negative influence of laser treatment on the mass and geometrical dimensions of the fibers, as well as their mechanical resistance to bending, stretching, and abrasion.…”
mentioning
confidence: 99%
“…20 The influence of the laser beam, this time of the ultraviolet (UV) type, on the physical and chemical properties of polyester as well as cotton fabrics was also investigated by Ayesh et al. 21…”
mentioning
confidence: 99%